1944
DOI: 10.1021/ja01236a037
|View full text |Cite
|
Sign up to set email alerts
|

A New Synthesis of α-Bromoaldehydes

Abstract: The dimer (100 mg.) was dissolved in acetic acid (8 cc.) containing hydrobromic acid (8 cc., 48%), and the solution was boiled for twenty minutes. The mixture rapidly became dark and no pure product could be isolated from it.Dithymoquinone (100 mg.) in ether (30 cc.) was shaken with a solution of sodium hydrosulfite (2 g.) in water (20 cc.) until the color was discharged (forty minutes). From

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1971
1971
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The kca t values were ),104 rain -1 (table 1), much slower than that of aromatic esters [5,6], but ~2 orders of magnitude faster than the amide analogue of acetylcholine (kca t = 2.2 X 102 min -l) [8]. EOH + H ÷ + CH3COO- (3) in which EOH is the AChE serine enzyme, EOCOCH 3 is the transient acetyl enzyme, k2 is acylation rate and k3 is deacylation rate constant.…”
Section: Aromatic Amidesmentioning
confidence: 95%
See 2 more Smart Citations
“…The kca t values were ),104 rain -1 (table 1), much slower than that of aromatic esters [5,6], but ~2 orders of magnitude faster than the amide analogue of acetylcholine (kca t = 2.2 X 102 min -l) [8]. EOH + H ÷ + CH3COO- (3) in which EOH is the AChE serine enzyme, EOCOCH 3 is the transient acetyl enzyme, k2 is acylation rate and k3 is deacylation rate constant.…”
Section: Aromatic Amidesmentioning
confidence: 95%
“…Phenothlazine-10-carbonyl chloride (PTCC, (a) in fig.l) o-nitro chloroacetanilide VII n-butanal and acetic anhydride [3], and tropolone acetate (VI, fig.l) from tropolone and acetic anhydride [4]. Hydrolysis rates of esters were followed pH-statically.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that with Et 3 B initiation, SF 5 Br adds easily to enol acetates, prepared by using either isopropenyl acetate with p ‐toluensulfonic acid11 or a mixture of potassium acetate and acetic anhydride,12 to form bromo‐SF 5 ‐acetates 8 as a 3:1 mixture of diastereomers (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…Dimethyl acetals 10 resulting from heating under reflux with methanol can easily be hydrolyzed to 9 (Scheme ) 13. Alternatively, direct hydrolysis of 8 by using a mixture of hydrochloric acid and glacial acetic acid is efficient 12. Attempts to use milder conditions with lithium halide or metal oxide salts were not effective 14.…”
Section: Resultsmentioning
confidence: 99%